Inventarisasi Tumbuhan Paku di Jalur Ciwalen Taman Nasional Gunung Gede Pangrango Jawa Barat - Fatahillah, Ibrahim; Fajar Lestari, Indri; Salsabila, Khairunnisa; Pratiwi, Ratna; Amalia, Tasya; Septiyaningsih, Ari; Kulsum, Umi; Hendi Ristanto, Rizhal; Sedayu, Agung (Biogenesis: Jurnal Ilmiah Biologi, 2018)
After being observed as a whole, Gunung Gede Pangrango National Park has a high diversity of Ferns. This research aims to describe Ferns in the Ciwalen Gunung Gede Pangrango National Park, so it is hopefully could describe the diversity of ferns in that path. The Inventory of ferns is done by using exploration method with random sampling technique which then identified with General Key to Malayan Fern referral. The results of this research showed that there are ten types of ferns that have been founded in the Ciwalen Gunung Gede Panggrango National Park, such as Sphaerostephanos sp., Asplenium truncata, Nephrolepis davallioides, Botrychium daucifolium, Selaginella opaca, Huperzia phlegmaria, Equisetum ramosissimum, Didymochlaena truncatula, Hymenophyllum sp., and Diplazium poliferum. Features any distinctive Ferns can be seen from the form such as  rhizome, type of  frond, an accessory, the sorus, habitats that were found, and others.